Practitioners’ perspectives on improving ready-to-eat food vending in urban Nigeria: a practice-based visioning and back-casting approach - Adeosun, Kehinde Paul; Greene, Mary; Oosterveer, Peter (Frontiers in Sustainable Food Systems, 2023)
In many parts of the world, food consumption is shifting from mostly home-based to out-of-home due to transforming of everyday lives as a result of urban development and changing infrastructure. This trend has spurred the expansion of informal ready-to-eat food vending, particularly among the urban poor. However, informal ready-to-eat food vending practices have faced challenges in provisioning menu settings with high energy and calories foods. Moreover, there are concerns about the safety, health, and diversity of food purchased through ready-to-eat food vending. This paper explores practice-oriented strategies, suggestions, and mechanisms through key actors’ experiences and perspectives to understand how the provisioning of healthy and diverse food in informal ready-to-eat food vending can be improved in urban Nigeria as a future transformative initiative. A social practice-oriented approach, combined with participatory future visioning and back-casting, was employed in a multi-phase process of interlinked focus group discussions and workshops involving key food sector stakeholders. The findings reveal that achieving an increase in diverse foods and integration of fruits and vegetables requires changing food norms and promoting sensitization to the importance of diverse diets through training initiatives involving primary actors. Additionally, key skills/competences in the provisioning of healthy and diverse foods need to be learned and relearned, while adequate food materials, finance and effective and efficient integration of the different food vending practice elements are required for the realization of these initiatives. Furthermore, understanding the relationships between food vending and other food-related provisioning practices within the food vending environment is essential in transitioning to healthier and more diverse food provisioning in the informal food vending sector. Our findings provide insights for policymakers to provide strategic pathways for practical interventions to improve food vending practices that meet the food security and nutritional needs of the urban poor.